Porous titanium manufactured by a novel powder tapping method using spherical salt bead space holders: characterisation and mechanical properties - Jia, Jiangang; Siddiq, Abdur R.; Kennedy, Andrew R. (Elsevier, 2015)
Porous Ti with open porosity in the range of 70–80% has been made using Ti powder and a particulate leaching technique using porous, spherical, NaCl beads. By incorporating the Ti powder into a pre-existing network of salt beads, by tapping followed by compaction, salt dissolution and “sintering”, porous structures with uniform density, pore and strut sizes and a predictable level of connectivity have been produced, showing a significant improvement on the structures made by conventional powder mixing processes. Parts made using beads with sizes in the range of 0.5-1.0 mm show excellent promise as porous metals for medical devices, showing structures and porosities similar to those of commercial porous metals used in this sector, with inter-pore connections that are similar to trabecular bone. The elastic modulus (0.86GPa) is lower than those for commercial porous metals and more closely matches that of trabecular bone and good compressive yield strength is retained (21MPa). The ability to further tailor the structure, in terms of the density and the size of the pores and interconnections has also been demonstrated by immersion of the porous components in acid.